A review of cold seeps in the Western Atlantic, focusing on Colombia and the Caribbean - Aguilar Pérez, Maria Isabel; Zapata-Ramírez, Paula A.; Micallef, Aaron (Frontiers in Marine Science, 2024)
Areas of the seafloor enriched with seeping fluids host unique chemosynthetic communities, and their interactions not only linked to the presence of oil and gas resources, but directly impact global geochemical cycles. These ecosystems can be found in diverse geological settings, spanning from passive to active continental margins, and encompass environments such as mid-ocean ridges, seamounts, cold brine lakes, mud volcanoes, and carbonate pinnacles. This review aims to examine seep environments in the Western Atlantic, the Caribbean, and Colombia, with a focus on understanding: I) their nature and origin, Itheir associated seabed characteristics, III) the biological communities directly connected to them, and IV) the chemistry and flow of the emitted fluids. The review identifies the close relationship of cold seeps to various geomorphological features, including linear diapir systems, salt diapirs resulting from salt tectonics, regions of mud volcanism, and compact seafloor mounds likely associated with buried mud diapirs. However, existing data on the fauna within these environments predominantly focus on megafauna, such as vestimentiferan tubeworms (Annelida), mussels, and vesicomyid bivalves (Mollusca), overlooking the crucial role of communities of small organisms, including fungi or macrofauna. This review highlights the absence of a consistent consensus among researchers regarding the factors controlling fauna distribution and presence in seep environments. Various authors have put forth divergent factors that influence seep community structures, with some emphasizing water depth, others the geological environment, and some the relationship with geomorphological conditions and fluid emissions. These findings underscore the need for further research into environmental factors and their roles in the observed distribution, presenting a promising avenue for future investigations.